Criticism of the Neoclassical Approach in Islamic Economic Policy in Indonesia - Maharatna Shifa Nurizka; Aufa Islami; Moh. Rofi’ieh; Haerunnisa; Muhammad Lathif Dzulfikar (Mahkota Science Publishers, 2025)
This study aims to open up space for reflection and debate on the need for a paradigm shift and new methods in developing Islamic economics in Indonesia. It uses a critical qualitative approach based on political economy theory and Critical Discourse Analysis (CDA) to examine the influence of the neoclassical paradigm on Islamic economic policy in Indonesia. The results indicate that critical reflection on the dominance of the neoclassical approach in Islamic economic policy in Indonesia reveals that Islamic economics remains trapped in epistemological and methodological subordination to the global capitalist system, often failing to realise the ideals of social justice, wealth distribution, and empowerment of vulnerable groups as mandated by the maqaṣid al-shari'ah. This phenomenon occurs because the success of Islamic economics is more often measured through neoclassical indicators that emphasise asset growth, efficiency, and market competitiveness, rather than substantive transformation of inequality and poverty structures. Nevertheless, this criticism should be viewed as a constructive call to rebuild the paradigm, decolonise Islamic economic knowledge, and reaffirm the agenda of social justice and empowerment of the ummah in every policy, innovation, and sharia institution.